An Analysis of Students' Problems in Writing Descriptive Text - Agustin, Agustin; Rianti, Wida Rianti; Asilestari, Putri (Journal of English Language and Education, 2024)
This study aims to analyze students' problems in writing descriptive texts. This research uses qualitative descriptive analysis. The population of this research is the 10th-grade students of SMKN 1 Bangkinang Kota in the 2022/2023 academic year, especially in class X Building Drawings. The sample was selected using a random cluster sampling technique, with only 1 class as the research sample. Data were collected using a written test, and the results of the test were analyzed using descriptive qualitative. The result of this study also showed that the students faced several problems in writing descriptive text. There were two kinds of problems found in students' writing; they were linguistic problems including grammar and vocabulary-related problems, and non-linguistic problems which include organization of ideas, content, and mechanical problems. The most frequently found problems in students' writing were related to grammar and mechanical. To overcome these problems, there are some suggested solutions which include using cooperative learning or rapid writing strategy in teaching writing descriptive text.